Cull cow carcass traits and risk of culling of Holstein cows and 3-breed rotational crossbred cows from Viking Red, Montbéliarde, and Holstein bulls - M. Piazza; M. Berton; N. Amalfitano; G. Bittante; L. Gallo (Journal of Dairy Science, 2023)
ABSTRACT: Culled dairy cows represent a considerable source of meat production, but their carcasses may vary greatly in quality because of the wide variation in the age, stage of lactation, breed, body condition, and other characteristics of the cows at slaughter. However, the effect of crossbreeding on the value of culled cows has so far received little investigation. The aim of this observational study was to compare a range of carcass attributes of cull cows from 3-breed rotational crossbreeding using Viking Red, Montbéliarde (MO), and Holstein (HO) bulls with those of HO purebred cows. Data on 1,814 dairy cows were collected. Cows were reared together in one herd and slaughtered in 4 slaughterhouses. The carcass weight, fleshiness, and fatness scores, the total value, and the price (€/kg) of each cow carcass were recorded. The culling of a few cows in the sample (n = 86) was classified by the farm manager as “urgent” following a diagnosis of injury or sickness, and this information was recorded. Carcass traits were analyzed with a mixed model which included the fixed effects of parity, days in milk, genetic group (purebred HO, 787 cows, and crossbred cows, classified according to the breed of sire within crossbreds, with 309, 428, and 290 cows sired by Viking Red, MO, and HO bulls, respectively), and interactions, and the random effects of month × year of the date of slaughter, and slaughterhouse. Logistic regression was used to investigate the association of parity, days in milk and purebred or crossbred origin with unplanned, “urgent” culling compared with regular culling. Average carcass weight across genetic groups was 297 ± 65 kg, average price €2.03 ± 0.53/kg, and average value €631 ± 269. Compared with HO, crossbred carcasses were 7 to 12% heavier depending on the breed of sire, were graded + 0.12 to + 0.28 units higher for fleshiness and + 0.26 to + 0.30 units higher for fatness, and fetched an 8 to 11% higher price. As a consequence, compared with purebred HO, carcasses from crossbreds had 15 to 24% higher value (€84 to €133 more per cow), with crossbred cows sired by MO showing the greatest values. Moreover, compared with the HO cows, the crossbred cows had a 37% lower risk of being urgently removed from the herd, which raises welfare concerns and may reduce the salvage value of cull cows. Because cull cows represent a supplemental source of income for dairy farmers, the greater overall value of crossbred cull cows should be taken into account in evaluating the economic effectiveness of crossbreeding schemes.